Introducing Jaga-rasa Jaga-tangga: A Community Program that Can Reduce Tuberculosis Stigma in Sleman, Indonesia - Purwanti, Nunuk Sri; Ghofur, Abdul; Khairani, Wittin; Sasmito, Priyo (PT Inovasi Pratama Internasional, 2024)
The low number of cases found compared to the incidence of Tuberculosis (TB) shows that the control of this disease becomes a serious problem. The stigma is suspected to be one of the obstacles to solving the TB problem in Indonesia. This study aims to analyze the ability of the Jaga-rasa Jaga-tangga program to decrease TB stigma in two Public Health Centers (PHCs) in Sleman Regency, Indonesia. This is a quasi-experimental study design with a control method. Both intervention and control groups get health education about TB stigma. The intervention group also gets an education about the Jaga rasa Jaga tangga (take care of your neighbors as well as take care of their feelings) program. The outcome measure was the TB stigma scale that measure before and after the intervention. Data were analyzed using paired t-tests and independent t-tests. 106 respondents were involved in this study divided into intervention and control groups. Age (p=0.006) and social status (p=0.015) are associated with TB stigma in the community. There were significant changes in the TB stigma scale after the intervention (paired =0.305; p=0.001). The Jaga-rasa Jaga-tangga program along with health education reduces TB stigma more effectively than health education only. Further studies are needed to confirm this result.